Autoantibody profile in myasthenia gravis patients with a refractory phase. Issue 5 (9th March 2022) - Veltsista, Dimitra; Kefalopoulou, Zinovia; Tzartos, John; Chroni, Elisabeth
Abstract: Introduction/Aims: A subgroup of myasthenia gravis (MG) patients fail to respond adequately to recommended treatments, a condition referred to as refractory MG. During the refractory phase, patients experience persistent debilitating symptoms with potential life‐threatening events or inability to reduce immunosuppressant dosages and minimize long‐term toxicities. Methods: We conducted a retrospective, single‐center study of 113 MG patients to investigate the autoantibody profile and clinical characteristics of refractory MG patients, compared with nonrefractory patients, based on predefined criteria. Results: Fifteen patients (13.3%) were classified as refractory. Double‐seronegative MG (DSNMG), without detectable nicotinic acetylcholine receptor (AChR) or muscle‐specific tyrosine kinase (MuSK) antibodies, was identified in six refractory patients, significantly higher than those with nonrefractory MG (40% vs 16.3%; P  = .031). None of the refractory patients had MuSK antibodies. Patients in the refractory group more frequently had an earlier disease onset, thymic pathology, and thymectomy ( P ≤. 03 for all). Discussion: In this study, patients with refractory MG were more likely than those with nonrefractory MG to be DSN; and refractory DSNMG patients had worse MGFA classes in their recent visit compared with anti‐AChR positive refractory patients. Refractory DSNMG patients may represent a distinct group that requires more individualized and targeted treatment approaches.